2019
DOI: 10.14254/2071-789x.2019/12-1/10
|View full text |Cite
|
Sign up to set email alerts
|

Value of work in the experience of the young generation of Visegrad countries

Abstract: The paper discusses the issues of experience and value of work, one of the elements of economic awareness of the young generation-students from the Visegrad countries. The paper presents the concept of work and its value according to Ronald Inglehart's value system. An analysis was carried out based on empirical research conducted in April-May 2015 and November 2016 in higher education institutions in the V4 countries (Poland: Katowice, Slovakia: Nitra, Czech Republic: Olomouc/Ostrava, Hungary: Gödöllő). 1 In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Since the research results have shown that it is hard to find a job in own country, maybe going abroad and having a chance to be seen on a global labour marker is a better option. Especially because, as our research show, students during studies are willing to take up a professional work, but it is a job that is incompatible with their education [18,19]. Labour market offers series of positions which enable to combine studies with professional work.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the research results have shown that it is hard to find a job in own country, maybe going abroad and having a chance to be seen on a global labour marker is a better option. Especially because, as our research show, students during studies are willing to take up a professional work, but it is a job that is incompatible with their education [18,19]. Labour market offers series of positions which enable to combine studies with professional work.…”
Section: Resultsmentioning
confidence: 99%
“…Working during studies shows their positive attitude towards it. As our research has shown, students take up work during studies for various reasons [18,19]. Diversification is most likely due to access to the labour market and employment possibilities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Undoubtedly, what also plays a role here is a respondent's individual situation connected with their place of work, financial, family situation and attachment to a given school (well-known rules, teachers, infrastructure, etc.). The similar research in the field also finds these features essential for the students' preferences, including their future work choice (Swadźba & Horáková Hirschler, 2019;Sułkowski et al, 2020). The authors do not exclude the fact that in the analyzed decision-making processes some latent variables that were not directly measured appeared additionally.…”
Section: Rankings As a Response To Challenges Of University Manageriamentioning
confidence: 89%